Acute Septic Arthritis: Open Drainage versus Needle Aspiration (Medical Forum Monthly, 2024)
Objective: This study aimsto compare the effectiveness of open drainage with needle aspiration in acute septic arthritis in our local population.Study Design: Randomized controlled trial.Place and Duration of study: This study was conducted in Orthopedics and Trauma unit, Khyber Teaching Hospital, Peshawar from Feb 2009 to Jan 2010.Materials and Methods: There a total of 114 patients that were randomly assigned to group A and B with 57 patients in each group. Group A was subjected to open drainage and Group B to needle aspiration. The effectiveness of intervention was assessed by the reduction of at least one grade of pain from the baseline on 7thpost-operative day.Results: In group A 26 (45.61%) and 31 (54.38%) patients had Grade 2 and Grade 3 pain respectively whereas in group B 28(49.12%) and 29(50.88%) patients had Grade 2 and Grade 3 pain respectively(p value 0.0025).Open drainage and needle aspiration in group A and B were effective in 49 (85.96%) and 39(68.42%) patients respectively (p value 0.0025).Conclusion: Open drainage is more effective than needle aspiration in patients with acute septic arthritis.